2020
DOI: 10.1371/journal.pone.0231264
|View full text |Cite
|
Sign up to set email alerts
|

Severe hyperbilirubinemia is associated with higher risk of contrast-related acute kidney injury following contrast-enhanced computed tomography

Abstract: Introduction Contrast-induced acute kidney injury (CI-AKI) is associated with high risks of morbidity and mortality. Hyperbilirubinemia might have some renal protection but with no clear cutoff value for protection. Related studies are typically on limited numbers of patients and only in conditions of vascular intervention. Methods We performed this study to elucidate CI-AKI in patients after contrast-enhanced computed tomography (CCT). The outcomes were CI-AKI, dialysis and mortality. Patients were divided to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…A prospective observational study reported an association between low bilirubin concentration and the composite of a two-fold increase in serum creatinine or ESRD requiring dialysis in Japanese patients with stages 3–5 CKD [ 12 ]. Nevertheless, some studies have reported opposite findings [ 13 , 34 , 35 ]. Majoni et al reported that a high bilirubin concentration was associated with a faster annual decline in eGFR but better renal outcomes in an Australian population [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective observational study reported an association between low bilirubin concentration and the composite of a two-fold increase in serum creatinine or ESRD requiring dialysis in Japanese patients with stages 3–5 CKD [ 12 ]. Nevertheless, some studies have reported opposite findings [ 13 , 34 , 35 ]. Majoni et al reported that a high bilirubin concentration was associated with a faster annual decline in eGFR but better renal outcomes in an Australian population [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study conducted in the United States also demonstrated associations between a high bilirubin concentration and low eGFR and increased albuminuria in healthy adults [ 34 ]. In addition, a large retrospective study reported that hyperbilirubinemia (total bilirubin > 2.0 mg/dL) was an independent risk factor for contrast-induced acute kidney injury, dialysis, and mortality after receiving contrast-enhanced computed tomography [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of liver diseases and hemolytic anemia was carried out according to 9th revision of the International Classification of Diseases code. Based on previous studies on bilirubin ( 15 , 16 ), Patients were stratified into two cohorts according to maximum concentrations of total bilirubin 24 h after admission as follows: (1) serum total bilirubin level < 2 mg/dL, (2) serum total bilirubin level ≥ 2 mg/dL. The primary outcome in the present investigation was in-hospital mortality.…”
Section: Methodsmentioning
confidence: 99%
“…Kidney function should be assessed before TIPS either through measurement of sCr or GFR (estimated or measured). 75,[158][159][160][161][162] A change in GFR may best capture changes in kidney function. The limitations of sCr in cirrhosis have been well documented (Supplementary Discussion section).…”
Section: Cardiopulmonary Renal and Neurologic Considerations In Transjugular Intrahepatic Portosystemic Shuntmentioning
confidence: 99%